An investigation of the traffic affecting the retail structure of the Claremont business centre - Wood, Sydney Passmore (School of Architecture, Planning and Geomatics, 2020)
Decentralisation of the cities throughout the world linked with the added mobility of the community due to the automobile has resulted in the phenomenal growth of the old satellite villages which were normally located at transportation nodes. To these new growth points must be added the true regional shopping centre set in the country and surrounded by its sea of parked vehicles. The regional centre has, as yet, not developed in South Africa but the phenomenon of decentralisation has stimulated the growth in certain of the old established local shopping areas surrounding the larger cities.